ANALISIS PENERAPAN METODE PROJECT BASED LEARNING DALAM MENINGKATKAN KOMPETENSI PERENCANAAN BISNIS KONSTRUKSI DAN PROPERTI DI SEKOLAH MENENGAH KEJURUAN - Ananda Surya Lesmana (CV. Adiba Aisha Amira, 2024)
This article intends to analyze the application of a project-based learning method that has an influence on vocational education with construction business planning subjects and property using literature review methods from various sources discussing project-based learning strategies against vocational subjects. Project- based learning methods are learning approaches that enable students to learn through hands-on experience in completing real projects or project simulations. In this model, students are given responsibility to plan, implement, and evaluate projects relevant to the subject matter learned, namely business planning and property in schools prevent vocational. With a focus on the context of vocational education, the research identifies the basic concepts of PJBL and evaluates its relevance in construction and property business planning subjects. Through critical analysis of relevant literature, the study also takes into account effective teaching strategies, challenges that may be faced, as well as added and negative values that arise from the application of PJBL to the improvement of student competence. The results of this study are shown so that it can provide deep insight into the potential of PJBL with the aim of improving vocational learning in SMK, as well as contributing to vocational education literature.